2005
DOI: 10.1614/ws-05-002r.1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply affects root:shoot ratio in corn and velvetleaf (Abutilon theophrasti)

Abstract: Competitive outcome between crops and weeds is affected by partitioning of new biomass to above- and belowground plant organs in response to nutrient supply. This study determined the fraction of biomass partitioned to roots vs. shoots in corn and velvetleaf in response to nitrogen (N) supply. Pots measuring 28 cm in diam and 60 cm deep were embedded in the ground and each contained one plant of either corn or velvetleaf. Each plant received one of three N treatments: 0, 1, or 3 g N applied as ammonium nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
86
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 17 publications
14
86
3
1
Order By: Relevance
“…Lindquist and Mortensen (1999) argued that velvetleaf causes corn yield loss primarily through competition for light, suggesting that leaf area and plant height are important canopy characteristics that determine the outcome of corn-velvetleaf competition. Both plant height and leaf area development can be influenced by the availability and competition for belowground resources (Bonifas et al 2005;Bonifas and Lindquist 2006;McCullough et al 1994;Radin 1983;Zhou et al 1997). Nitrogen (N) addition has a positive effect on both corn and velvetleaf growth, but velvetleaf height, leaf area index (LAI), and biomass tend to respond more to N addition than corn (Barker et al 2006).…”
mentioning
confidence: 99%
“…Lindquist and Mortensen (1999) argued that velvetleaf causes corn yield loss primarily through competition for light, suggesting that leaf area and plant height are important canopy characteristics that determine the outcome of corn-velvetleaf competition. Both plant height and leaf area development can be influenced by the availability and competition for belowground resources (Bonifas et al 2005;Bonifas and Lindquist 2006;McCullough et al 1994;Radin 1983;Zhou et al 1997). Nitrogen (N) addition has a positive effect on both corn and velvetleaf growth, but velvetleaf height, leaf area index (LAI), and biomass tend to respond more to N addition than corn (Barker et al 2006).…”
mentioning
confidence: 99%
“…These results are somewhat surprising since the C 4 photosynthetic pathway used by corn has greater photosynthetic efficiency (greater carbon gain per unit leaf area) than the C 3 velvetleaf (Lindquist 2001a). However, Bonifas et al (2005) and Harbur and Owen (2004) showed that corn had smaller leaf area ratio (leaf area per unit total biomass) than velvetleaf at similar sampling times. Therefore, the C gain per unit aboveground biomass may be smaller in corn because corn invests a greater proportion of its aboveground biomass in stem tissue than velvetleaf.…”
Section: Resultsmentioning
confidence: 93%
“…Bonifas et al (2005) showed that velvetleaf root biomass was always smaller than that of corn but that velvetleaf partitioned proportionally more biomass to roots than corn between 2 and 6 wk after planting when N supply was limiting. The combination of greater velvetleaf nitrogen uptake efficiency and increase in biomass partitioning to velvetleaf roots explains the greater velvetleaf whole plant [N] despite the smaller total root biomass throughout the experiment in both years.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(Mitskas et al 2003) and velvetleaf (Abutilon theophrasti Medic.) (Bonifas et al 2005). The competitive ability of volunteer wheat can be attributed to the fact that it was well established at the time of corn emergence.…”
Section: Resultsmentioning
confidence: 99%